Il risveglio dei sensi nel corpo dell’attore. Uno sguardo al teatro fisico della Grecia contemporanea (Itinera, 2017)
This study is an exploration of Modern Greek theatre. Nowadays in Modern Greek theatre we see many recreated, reformed theatre language forms, emphasizing actor’s body fundamental potentials. They seem to be an attempt, during the financial and social crisis, to assign mostly to art the role of supporting human culture. This is maybe the best era Greek theatre is experiencing. Theatre appears as the dominant artistic expression of Greeks, inside the spectrum of “physical” or “formal” theatre. The beginnings of this theatre date back to the Ancient Greek mimic, continuing through the Commedia dell'Arte renaissance, until the 20th century, when important artists began to deal with the actor’s body forces, embedding new experienced theories.